Mapping the Landscape of Self-regulated Learning with Interventions – A Bibliometric Guide for Academic Decision-Making - Chandy, Marina; Pavan Kumar, S. (Journal of Engineering Education Transformations, 2026)
Research indicates that novice learners often struggle to plan, monitor and evaluate their cognitive processes during academic tasks, limiting their ability to engage meaningfully with the content. This challenging gap underscores the need for educational paradigms that cultivate learner autonomy and support lifelong learning. Self-regulated learning (SRL) offers a promising pathway to address this need by integrating metacognitive, behavioral, and motivational components to foster sustainable self-regulated skills.To trace the evolution of SRL research-particularly in relation to interventions, this study conducts a bibliometric analysis, to map its academic trajectory. Using Scopus and WoS databases, 1151 documents from 2000 to 2025 were analysed using VOS viewer and RStudio-Biblioshiny. The objective of this study is to guide researchers in understanding and analyzing scientific production, thematic co-occurrence patterns, evolving publication trends , influential authors, countries and affiliations in the domain .The analysis reveals a significant surge in scaffolded intervention driven SRL research with developed nations leading the way. This highlights the need to integrate such practices in a contemporary pedagogical approach. These insights provide a foundation for policymakers and academic decision makers to synthesize literature and adopt this emerging educational model. In turn, this would help foster a proactive learning culture aligned with emerging paradigms and will help support a seamless transition from academic environments to the workplace.